Pengaruh Pupuk Kompos Ampas Tebu Terhadap Pertumbuhan dan Produksi Jagung Manis (Zea mays saccharata Sturt) Tumpangsari dengan Kedelai (Glycine max L. Merrill) - Randi Saputra; Chairil Ezward; Seprido Seprido (Program Studi Agroteknologi Fakultas Pertanian Universitas Andalas, 2022)
Intercropping is an effort to plant several types of plants on the same land and time, which are arranged in rows of plants. The purpose of this study was to determine the effect of sugarcane bagasse compost on the growth and production of sweet corn (Zea mays saccharata) intercropping with soybeans (Glycine max L. Merrill.). The design used in this study was a non-factorial randomized block design (RAK), namely bagasse compost (S) which consisted of 5 levels, namely: S0: Without sugarcane bagasse compost fertilizer (Control), S1: Sugarcane bagasse compost fertilizer. 10 tons/ha (1.92 kg/plot), S2 : Application of 20 tons/ha bagasse compost (3.84 kg/plot), S3 : Application of 30 tons/ha (5.76 kg/ha) bagasse compost plot), S4 : Application of 40 ton/ha of bagasse compost fertilizer (7.68 kg/plot). Based on the research that has been carried out, the treatment of giving sugarcane bagasse compost has a significant effect on the weight of sweet corn cobs 371.12 grams and the weight of the cobs without sweet corn husks is 279.15 grams, the best treatment is in S4, namely the application of 40 ton/ha (7.68 kg/plot). While the soybean plant height was 79.75 cm and the dry weight of soybean seeds was 22.97 grams, where the best treatment was in S3 namely the application of 30 tons/ha of bagasse compost (5.76 kg/plot).